FARM FAMILIES AND FUTURE OPTIONS – THE ROLE OF THE EXTENSION ADVISORY SERVICE IN SHAPING IRISH AGRICULTURE - McDonagh, John; Farrell, Maura; Mahon, Marie (Quaestiones Geographicae, 2013)
Agriculture across Europe is very much driven by the reforms initiated by the European Union (EU) and World Trade Organisation negotiations. Reforms have mobilised a shift in agricultural practices from production to a somewhat contested post-production and, more recently, multifunctional agriculture regime. Accompanying such change has been the debate on the future of farming, the role of agriculture within the countryside, and the extent to which the sector will maintain support from the Common Agricultural Policy (CAP) and the EU. Central to these discussions, in terms of bringing about beneficial change on farms and in rural areas, is the advice and direction available to farmers. The agricultural extension advisory services are an integral component of this process. This paper explores the position of public extension advisory services in Ireland and determines the extent to which these services are impacting the trajectory of modern agricultural practices within a framework of more traditional views of farmers and farm families.